Seed Maturity and Pollen Source Influence on Dura X Pisifera (Elaeis Guineensis Jacq.) Seed Quality - Lwin, Naing Maw (2010)
In this study, the effects of pollen source and seed maturity and size on germinability and vigor of oil palm (Elaeis guineensis Jacq.) seeds were investigated. Seeds were obtained from controlled pollinated bunches of selected Deli dura with pisifera (AVROS) palms. Experimental design used was randomized complete block design (RCBD) with three replications. The treatments were two pollen sources: 8-year and 27-year old palms, six stages of seed maturity: 13, 15, 17, 19, 21 and 23 weeks after pollination (WAP) and three classes of seed size: small, medium and large. For seed germination, ‘Dry Heat Treatment Method’ was used. Daily data collection was extended up to 60 days starting from first sign of germination. The seed germination parameters recorded were final cumulative germination percentage (FGP), mean time to complete germination (MTCG), average germination speed (AGS), germination value (GV) and vigor index (VI). Some seed traits of shell thickness and ratio to seed weight (SR), 100-seed weight and moisture content, dry and fresh weight of kernel and embryo from different maturity treatment levels of both pollen sources were also recorded. Analysis of variance was done with SAS 9.2 software. Means were separated using Tukey's Honestly Significant Difference (HSD) test at 5% level of probability. The results showed that the oil palm seeds harvested at 21 WAP had both the highest FGP and GV with fastest AGS. It could be defined that 21 WAP was the physiological maturity stage of oil palm seeds because FGP was at its maximum value. There were no statistically significant differences in all parameters of seed germination and vigor between 21 WAP and 23 WAP, whereas 23 WAP had relatively larger VI for consecutive seedling growth. Therefore, 23 WAP could also be defined to be the harvest maturity stage for oil palm seed. In addition, the influence of pollen source on germinability and vigor was significantly different at all maturity stages tested except at 23 WAP. Immature seeds up to 15WAP showed no germination at all. Seeds which resulted from pollination with pollen from 8-year old palm had higher seed germination potential (FGP) than those seeds produced from pollination with pollen from 27-year old palm at 21 WAP. Similar pattern was observed for MTCG, AGS and GV of seeds. However, seeds produced from pollination with pollen from 27-year old palm possessed superior potential of FGP, MTCG, AGS, GV and vigor (VI) for seedling growth rate at 19 WAP. Variations in seed size did not seem to significantly affect the germination capacity and vigor. Thus, all sizes of seed could be utilized as commercial planting materials. However, further studies on seed size effect on germination and vigor in relation to other factors especially genetic control is still needed for oil palm seed germination process.